Identification and validation of key molecules associated with humoral immune modulation in Parkinson’s disease based on bioinformatics - Xing, Na; Dong, Ziye; Wu, Qiaoli; Kan, Pengcheng; Han, Yuan; Cheng, Xiuli; Zhang, Biao (Frontiers in Immunology, 2022)
Objective: Parkinson’s disease (PD) is the most common neurodegenerative movement disorder and immune-mediated mechanism is considered to be crucial to the pathogenesis. Here, we investigated the role of humoral immune regulatory molecules in the pathogenesis of PD. Methods: Firstly, we performed a series of bioinformatic analyses utilizing the expression profile of peripheral blood mononuclear cell (PBMC) obtained from GEO database (GSE100054, GSE49126 and GSE22491) to identify differentially expressed genes related to humoral immune regulatory mechanisms between PD and healthy controls. Subsequently, we verified the results using quantitative polymerase chain reaction (Q-PCR) and enzyme-linked immunosorbent assay (ELISA) in clinical blood specimen. Lastly, Receiver operating characteristic (ROC) curves were performed to determine the diagnostic effects of verified molecules. Results: we obtained 13 genes that mainly associated with immune-related biological processes in PD by bioinformatic analysis. Then, we selected PPBP, PROS1 and LCN2 for further exploration. Fascinatingly, our experimental results don’t always coincide with the expression profile. PROS1 and LCN2 serum levels were significantly higher in PD patients compared to controls (p < 0.01 and p < 0.0001). However, PPBP serum level and expression in PBMC of PD patients was significantly decreased compared to controls (p < 0.01 and p < 0.01). We found that PPBP, PROS1 and LCN2 with an area under the curve (AUC) of 0.663 (95%CI: 0.551-0.776), 0.674 (95%CI: 0.569-0.780) and 0.885 (95%CI: 0.814-0.955). Furthermore, in the biological processes term of Gene ontology (GO) analysis, the three molecules were all involved in humoral immune response (GO:0006959). Conclusions: In general, PPBP, PROS1 and LCN2 were identified and validated to be related to PD and PPBP, LCN2 may potentially be biomarkers or therapeutic targets for PD. Our findings also provide some new insights on the humoral immune modulation mechanisms in PD.